Peningkatan Praktik Cuci Tangan Pakai Sabun pada Anak Usia Sekolah dengan Metoda Emo Demo - Dahlia Indah Amareta; Efri Tri Ardianto (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Indonesian people's habits, including children in hand washing with soap, are still low, despite of it is one of the most effective ways to prevent diarrhea and ARI, which are the leading cause of child death. Emotional Demonstration (Emo Demo) is one of the imaginative and provocative educational methods to achieve healthy behavior. The purpose of this study was to analyze the effect of hand washing with soap counseling with Emo Demo method on school-age children in Islamic Elementary School Al-Badri, in Kalisat, Jember District. This research was a quantitative one that used pre experiment with one group pre-test post-test design, and consisted of 47 stu-dents as research subject. The variables under study were the knowledge and practice of hand washing with soap. The data collection was conducted in September-October 2017. Prior to the intervention, most of the students were lack of knowledge and practice (78,8 % and 85,1 %). Af-ter the intervention was done by providing counseling, small group demonstration, and provision of handwashing facilities, most students had moderate knowledge (76,6 %), while students with good knowledge were as much as 8,5 %. The practice of hand washing with soap among study subjects were mostly in good category (76,6%). To conclude, there is a significant knowledge dif-ferent between before and after intervention (p<0,001), and so is the practice (p< 0,001).